Fluxless Direct Soldering of Transparent Conductive Oxides (TCOs) to Copper - Lung-Chuan Tsao; Cheng-Kai Li; Yu-Kai Sun; Shih-Ying Chang; Tung-Han Chuang (Advances in Materials Science and Engineering)
Due to the combined advantages of low cost, good soldering properties, and appropriate melting temperature range, novel Sn8Zn3Bi1Mg active solder was developed for direct soldering of transparent conductive oxide (TCO) ceramic targets with oxygen-free copper at 200°C in air. The TCO specimens have aluminum-doped zinc oxide (AZO) and zinc oxide (ZnO) ceramics. The direct soldering process was performed without the need for flux or pre-metallization of the two transparent conductive oxides. The microstructure, phase constitution, melting characteristics, and soldering properties of the Sn8Zn3Bi1Mg active solder were investigated. The liquidus temperature of the Sn8Zn3Bi1Mg active solder was 198.6°C, which was very close to the binary Sn-Zn eutectic temperature of 198.5°C. The effect of temperature on the bonding strength of the solder joints was evaluated. The shear strengths of AZO/Cu and ZnO/Cu joints soldered with Sn8Zn3Bi1Mg active solder were 10.3 and 7.5 MPa at room temperature, respectively. Increasing the temperature from room temperature to 180°C reduced the bonding shear strengths of AZO/Cu and ZnO/Cu joints to 3.3 and 3.7 MPa, respectively.